A Study on the Application of Random Matrix Theory in the Construction of the Evaluation System of Public English Flipped Classroom Teaching in Higher Education Institutions. (5th September 2022) - Sun, Xuemei; Lin, Xun
Abstract : With the development of science and technology, the advent of the knowledge era, the Internet era, the WeChat era, and the mobile era as well as the development of multimedia have brought about great changes in the dissemination, communication, construction, and sharing of knowledge. This series of changes has led to unprecedented changes in teaching philosophy, teaching mode, teaching objectives, teaching design, teaching methods, and teaching approaches in higher vocational education. With the deepening of the new round of curriculum reform, flipped classroom teaching has been generally accepted and widely used. Therefore, it is essential to evaluate flipped classroom teaching. Based on the introduction of the random matrix theory, this paper attempts to establish a complete and scientific evaluation index system in conjunction with the flipped public English classroom in higher education institutions, so as to provide students and teachers with a reliable means of evaluation and thus promote the practical application of English teaching in higher education.